Study of Nitrogen Nutrient Absorption and Forage Production in Kalopo Plants (Calopogonium mucunoides) - Triputra, Kustiawan; Mansyur, Mansyur; Susilawati, Iin; Aditya, Irfan Dwi (Fakultas Peternakan, Universitas Padjadjaran, 2025)
AbstractThis research aims to evaluate differences in soil nitrogen content, nitrogen absorption by plants, and forage production of Calopogonium mucunoides plants grown on andosol and ultisol soils during a 90-day planting period. The research method used was experimental, with treatment factors in the soil type (andosol and ultisol). The parameters observed included the soil’s moisture, temperature, pH, nitrogen content, and the plant’s nitrogen content and forage production. The results showed that Andosol's average soil moisture value (53.61%) was higher than Ultisol (43.68%). The soil temperature of Ultisol (24.34°C) tends to be higher than Andosol (23.36°C). Andosol soil pH (5.04) exceeds Ultisol's (4.87). The soil nitrogen content in Andosol (4,838%) is higher than in Ultisol (4,058%). The nitrogen content in plant tissue in both soil types is relatively the same, namely (2.423%) for andosol soil and (2.523%) for ultisol soil. However, forage production on Andosol (42.65 g/pot fresh weight; 11.85 g/pot dry weight) was almost 2 times higher than Ultisol (21.75 g/pot fresh weight; 5.907 g/pot dry weight). Nitrogen uptake in andosol soil is 0.247 grams/pot, higher than in ultisol soil, 0.149 grams/pot. In conclusion, Andosol is more optimal for the growth of C. mongoides in forage production.